Adobe Acrobat DC Pro advanced - Uscilka, Deb; Safari eBooks ([Place of publication not identified] : Intellezy, 2016)
"In this course, students will learn to use advanced document tools and modify document properties, compare documents, enhance scans, as well as enhance documents by adding rich media such as sound, video, and interactive buttons. Students will learn to use the measurement tool, the distance tool, the perimeter tool and the area tool. Students will create interactive forms from a Word document or InDesign document, add form elements, add check boxes and radio buttons, and distribute forms for feedback. Students will understand the importance of accessibility and test for accessibility. Finally, students will understand signatures, create signatures, and add signatures to a document. "--Resource description page.
Title from resource description page (Safari, viewed January 27, 2017).
Presenter, Deb Uscilka.
Keywords: Adobe Acrobat; Cloud computing; Electronic books